Design Optimization of HANARO Irradiation Capsule for Long-Term Irradiation Testing - Kee Nam Choo; Man Soon Cho; Seong Woo Yang; Byung Hyuk Jun; Myong Seop Kim (Science and Technology of Nuclear Installations)
As HANARO has been recently required to support new R&D relevant to future nuclear systems requiring much higher neutron fluence, two types of bottom rod tip of the capsule were preliminarily prepared. The first one is a conventional design made of STS304 and welded using a tungsten inert gas (TIG) welding method. The other is a new design made of STS316L and welded using electron beam (EB) welding to strengthen the fatigue property of the rod tip. During the out-pile testing, they failed after 40 and 203 days, respectively. The fracture surfaces were examined using microscopes and the maximal applied stresses were estimated. The combination of these stresses was proved to be sufficient to cause a fatigue failure of the rod tip of the capsule. Based on the failure analysis, an optimized design of the rod tip of the capsule was made for long-term irradiation testing. It was designed to improve the welding and fatigue properties, to decrease the applied stress on the rod tip, and to fundamentally eliminate the effect of residual stress due to welding. The newly designed capsule was safely out-pile-tested up to 450 days and will be utilized for HANARO irradiation testing.